Green Synthesis and Evaluation of 5-(4-Aminophenyl)-4-Aryl-4H-1, 2, 4-Triazole-3-Thiol Derivatives: Green synthesis and evaluation of 5-(4-aminophenyl)-4-aryl-4H-1, 2, 4-triazole-3-thiol derivatives - Vikas Gopalrao Rajurkar; Sagar M. Shirsath (Iranian Journal of Pharmaceutical Sciences, 2017)
The green synthesis of 5-(4-aminophenyl)-4-aryl-4H-1,2,4-triazole-3-thiol was achieved in four steps. In the first step, 4-amino benzoic acid was refluxed in ethanol along with catalyst Conc. Sulphuric acid to produce ethyl-4-amino benzoate I. Further compound I was refluxed with hydrazine hydrate in ethanol to produce 4-amino benzohydrazide II. Compound II was refluxed in ethanolic potassium hydroxide with carbon disulfide to produce 5-(4-aminophenyl)-1, 3, 4-oxadiazole-2-thiol III. Compound III refluxed in ethanol with different substituted primary aryl amine gave title compounds 5-(4-aminophenyl)-4-aryl-4H-1, 2, 4-triazole-3-thiol IVa-o. The compounds obtained were identified by FT-IR, 1H-NMR, GC- mass spectroscopy data, and elemental analysis and also screened for in-vivo antimicrobial activity. In vitro antibacterial activity was carried out against organisms like E.coli. K.pneumonia, S.aureus, and B.subtilis as well as in vitro antifungal activity were carried out against organisms like A.niger and S.cerevisiae. In vitro antimicrobial evaluation, the most potent broad spectrum compound IVc, IVd, and IVf were found significant agent against standard drug Norfloxacin and Ketoconazole.